Structure effect and orientation distribution of azo dyes on optical anisotropy of dyed PVA-films - Filippovich, L.N.; Ariko, N.G.; Almodarresiyeh, H.A.; Shahab, S.N.; Malashko, P.M.; Agabekov, V.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The derivatives of phenylazobenzoic, phenylazosalicylic acids and azobenzeneazonaphthalene were synthesized and employed to prepare polarizing films based on polyvinyl alcohol (PVA). The single-piece transmittance (T0), polarizing efficiency (PE), dichroic ratio (Rd) of films and order parameter of dyes (Sdye) were calculated. It was found that parameters Rd and Sdye increased as electron-donating of substituents in molecules of phenylazobenzoic and phenylazosalicylic acids derivatives was grown, and the polarizing efficiency of film increased with increasing the order parameter of dye. Development of PVA films dyed with the derivatives of phenylazosalicylic acid and azobenzeneazonaphthalene allowed to obtain polarizers for near UV and visible range of spectrum, respectively. It was also developed a broadband polarizer for 300-610 nm.